Dimensions of creativity - Boden, Margaret A. (Cambridge A Bradford Book, 1996)
Dimensions of Creativity brings together original articles that draw on a range of disciplines -- from the history and sociology of science, psychology, philosophy, and artificial intelligence -- to ask how creative ideas arise, and whether creativity can be objectively defined and measured.Margaret Boden and her colleagues Simon Schaffer, Gerd Gigerenzer, David N. Perkins, Howard Gardner, Colin Martindale, and Hans J. Eysenck demonstrate that creativity requires not only challenging new ideas but their acceptance by some relevant social group. Although some new ideas can arise as novel associations, others are generated by exploiting structural features of an existing conceptual space. Strong motivations often drive the creators and those who evaluate and perpetuate their work.The seven essays -- although very different -- are complementary. The book can serve as an up-to-date introduction to the study of creativity in various disciplines. The many references provide a way into the relevant literature.A Bradford BookShow More Show Less